Cats just want to have fun: Associations between play and welfare in domestic cats. (27th January 2023) - Henning, Julia; Nielsen, Torben; Fernandez, Eduardo; Hazel, Susan
Abstract: Play is often considered an indicator and promotor of animal welfare and may facilitate closer cat-human relationships. However, few studies have empirically investigated these associations. The current study aimed to investigate play-related factors associated with four welfare outcome measures in cats ( Felis catus ) including: cat quality of life; cat-guardian relationship quality; problem behaviour prevalence; and behavioural changes. An online survey was developed using demographic information, questions related to play and resources, free text sections and the following validated measures: cat quality of life (QOL), the cat owner relationship scale, and the adult playfulness trait scale. Responses were completed by 1, 591 cat guardians from 55 countries. Higher cat playfulness scores and a greater number of games played were significantly associated with higher cat QOL scores while longer amounts of daily play, greater number of games, both cat and guardian initiating play and higher guardian playfulness scores were all significantly associated with higher cat-guardian relationship scores. Exclusively indoor housing was significantly associated with both higher cat QOL and higher cat-guardian relationships scores compared to cats with outdoor access. Behavioural changes associated with distress in cats were reported when play was absent. Play may be an important factor in assessing and maintaining cat welfare. Further research into the mechanisms of how play impacts welfare and cat-guardian relationships is needed.